Foam iron-nickel surface in-situ growth platinum modified nickel-iron layered double hydroxide bifunctional material and preparation method and application of foam iron-nickel surface in-situ growth platinum modified nickel-iron layered double hydroxide bifunctional material

By growing platinum-modified nickel-iron layered double hydroxide material on the surface of foam iron nickel, the problems of high overpotential and high energy consumption during the electrolytic hydrogen production process are solved, and the efficient preparation and stability of dual-function catalysts are achieved , simplifies the process flow and is suitable for large-scale production.

CN119243227APending Publication Date: 2025-01-03CHANGZHOU UNIV

Patent Information

Application Number
CN202411181141.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art In the process of electrolyzing water hydrogen production, the high overpotential and large energy consumption of alkaline electrolyzed water leads to high hydrogen production costs, and the existing bimetallic hydroxide catalyst preparation methods are complex and are not conducive to large-scale production.

Method used

Using platinum-modified nickel-iron layered double hydroxide material with platinum-modified iron foam nickel on the surface of iron foam nickel, the metal iron foam nickel is heated in an acidic solution containing a chloroplatinic acid precursor to obtain solid platinum metal nanoparticles. The nickel-iron layered bimetallic hydroxide nanosheets realize the preparation of bifunctional catalysts, avoiding the need for additional nickel ions and iron ion salts.

Benefits of technology

The dual-function electrode that can electrolyze water hydrogen and oxygen evolution reaction under alkaline conditions has excellent activity and stability, reduces the amount of precious metal platinum, avoids catalyst loss and resistance problems caused by binders, and simplifies preparation Process suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243227A_ABST
    Figure CN119243227A_ABST
Patent Text Reader

Abstract

The invention discloses a foam iron-nickel surface in-situ growth platinum modified nickel-iron layered double hydroxide bifunctional material and a preparation method and application thereof.The preparation method comprises the steps that a foam iron-nickel substrate is immersed in an acid solution containing chloroplatinic acid, heating treatment is conducted for a certain period of time, and then the nickel-iron layered double hydroxide bifunctional material is obtained; and a nickel-iron layered double-metal hydroxide mixed material modified by platinum nanoparticles grows on the surface of the foam iron-nickel in situ. In the preparation process of the one-step method, nickel ions or / and iron ion salts and sacrificial agents do not need to be additionally added, atom economy is good, reaction conditions are mild, energy consumption is low, and meanwhile the problem that the catalyst is prone to falling off due to multiple times of operation and washing is solved. The platinum / ferronickel layered bimetal hydroxide / foam iron nickel electrode prepared by the method shows excellent hydrogen production and oxygen production activity in an alkaline water electrolysis reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material preparation, and specifically relates to a nickel-iron layered double hydroxide dual-functional material modified by in-situ growth of platinum on the surface of nickel-iron foam, and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is increasingly regarded as the cornerstone of clean energy. The process of hydrogen production by electrocatalytic water decomposition under alkaline conditions is environmentally friendly and has no carbon emissions. It is considered to be an effective strategy to address climate change and energy shortages (Nat. Mater., 2024, 23: 252-261). However, due to the high overpotential and high energy consumption of alkaline water electrolysis, the cost of hydrogen production is relatively high and it has not yet been widely used (Bioresource Tech., 2021, 319: 124175). Therefore, the development of efficient electrocatalysts is crucial to reducing the cost of hydrogen production by water electrolysis and realizing economically feasible hydrogen production projects by water electrolysis.

[0003] The water electrolysis process includes hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), and OER is often the rate-determining step in water electrolysis due to its inherently slow four-electron transfer process in the process of oxidizing OH- to O2 (J. Colloid Interface Sci., 2024, 657: 83-90). Bimetallic iron-nickel hydroxide is considered to be one of the most promising non-precious metal catalysts for OER in alkaline solutions (Angew. Chem. Int. Ed., 2018, 58: 1252-1265). In addition, in alkaline solutions, the combination of platinum and hydroxide can solve the problem of slow dissociation of metal platinum to water and improve the HER activity of Pt in alkaline solutions (Appl. Catal. B: Environ., 2022, 316: 121654). Therefore, combining lower loadings of platinum and nickel-iron hydroxide can simultaneously improve the catalytic activity of HER and OER, greatly reducing the overpotential in the water electrolysis process.

[0004] Nickel foam (NF) has a three-dimensional (3D) porous structure, which can effectively promote the release of bubbles, thereby preventing the active sites from being blocked, and therefore has received widespread attention in the field of alkaline water electrolysis. In addition, compared with the electrodes in which powder catalysts need to be fixed with a binder on a conductive substrate, catalysts grown directly on the substrate tend to have higher stability and conductivity. In previous work, a method for growing platinum-modified Ni(OH)2 nanosheets on the surface of NF under mild conditions was developed (Appl.Surf.Sci., 2023, 629:157433, CN117987843A). The resulting Pt / Ni(OH)2 / NF electrode has good hydrogen evolution performance under alkaline conditions, but due to the lack of high-valent metal ions, the oxygen evolution performance is not ideal.

[0005] In the patent "Method for preparing nickel-iron layered double metal hydroxide material on the surface of nickel-iron foam" with publication number CN117385396A, although nickel ions and iron ion salts do not need to be added during the preparation process, sacrificial agents such as cobalt salts and sulfates need to be added to corrode the metal iron-nickel substrate. This preparation method will introduce cobalt ions and sulfate ions in the solution into the prepared material to become doping substances. In addition, the application of the material prepared by this invention is limited to oxygen evolution reaction. In the patent "A nickel foam-supported nickel-iron bimetallic hydroxide composite catalyst and its preparation method and application" with publication number CN114643057A, by heat-treating nickel foam in a mixed solution containing iron precursor ferric chloride hexahydrate, anhydrous sulfuric acid and deionized water, a nickel-iron double hydroxide composite catalyst grown on the surface of nickel foam is obtained, and this catalyst is used in the dynamic capture and photocatalytic purification of pathogenic microorganisms on inactivated bioaerosols. In the patent "Bifunctional catalyst for water electrolysis based on nickel-iron foam and its preparation method" with publication number CN116949494A, nickel-iron oxide nanosheets are first grown on the surface of nickel-iron foam, and then a vanadium-doped nickel-cobalt layered double hydroxide intermediate is grown by hydrothermal method, and finally vanadium-doped nickel-cobalt phosphide nanosheets are synthesized by plasma chemical vapor deposition. Although the material of this invention has the dual functional characteristics of hydrogen and oxygen evolution, its steps are relatively complicated, the experimental method is costly, and it is not conducive to scale-up production. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a nickel-iron layered double hydroxide bifunctional material by in-situ growth of platinum modified on the surface of nickel-iron foam.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a dual-functional nickel-iron layered double hydroxide material with in-situ growth of platinum modified on the surface of nickel-iron foam, comprising:

[0010] The metal foamed nickel iron is placed in an acidic solution containing a chloroplatinic acid precursor and subjected to a heating treatment to obtain nickel-iron layered double metal hydroxide nanosheets with platinum metal nanoparticles immobilized on the surface of the metal foamed nickel iron.

[0011] As a preferred embodiment of the preparation method of the present invention, the acidic solution containing the chloroplatinic acid precursor is composed of an ether compound, an alcohol compound and water, and the volume ratio of ether, alcohol and water is (2:7:1) to (5:2:3).

[0012] As a preferred embodiment of the preparation method of the present invention, the ether compound comprises one or more of ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, diethylene glycol diethyl ether and n-butyl ether;

[0013] The alcohol compound includes one or more of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, and glycerol.

[0014] As a preferred embodiment of the preparation method of the present invention, the pH value of the acidic solution is 1-6.

[0015] As a preferred embodiment of the preparation method of the present invention, the chloroplatinic acid precursor is a chloride, nitrate and carbonate of platinum, including chloroauric acid, potassium chloroaurate, sodium chloroaurate, ammonium chloroaurate, chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, platinum chloride, potassium chloroplatinite, sodium chloroplatinite, diethylamine platinum chloride, platinum nitrate, ammonium tetrachloroplatinate, ammonium chloropalladate, sodium chloropalladate, potassium chloropalladate, ammonium chlororhodate, sodium chlororhodate, potassium chlororhodate, chloroiridic acid, sodium chloroiridate, potassium chloroiridate, rhodium trichloride, ruthenium trichloride, cupric chloride and cuprous chloride.

[0016] As a preferred embodiment of the preparation method of the present invention, in the metal foam iron-nickel, the weight ratio of iron to nickel is 0-1, excluding 0 and 1.

[0017] As a preferred embodiment of the preparation method of the present invention, the weight ratio of iron to nickel in the metal foam iron-nickel is 3:7.

[0018] As a preferred embodiment of the preparation method of the present invention, the temperature of the heating treatment process is 0 to 200° C. and the time is 0 to 24 hours.

[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a nickel-iron layered double hydroxide bifunctional material electrode with platinum modified by in-situ growth on the surface of nickel-iron foam.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide the use of the electrode in the electrolysis of water under alkaline conditions to produce hydrogen and oxygen.

[0021] Beneficial effects of the present invention:

[0022] (1) The platinum / nickel-iron layered double metal hydroxide / foamed iron-nickel ternary composite electrode prepared by the method is a bifunctional electrode, which has excellent activity and stability as a hydrogen evolution electrode and an oxygen evolution electrode for water electrolysis under alkaline conditions;

[0023] (2) The present invention adopts a one-step method to immerse the foamed iron-nickel substrate in an acidic solution of ether containing chloroplatinic acid without adding additional nickel ions and / or iron ion salts. By heating for a certain period of time, a nickel-iron layered double hydroxide mixed material modified with platinum nanoparticles is in situ grown on the surface of the foamed iron-nickel.

[0024] (3) The present invention does not require the high temperature and high pressure preparation conditions of the traditional hydrothermal method, has low equipment requirements, and does not require the additional addition of nickel ion salts, iron ion salts, and sacrificial agents. The present invention effectively avoids the addition of metal salt sacrificial agents, thereby achieving the successful preparation of pure and undoped bifunctional electrodes; relying on the oxidizing ability of proton acid to oxidize metallic nickel and metallic iron into nickel ions and iron ions, a nickel-iron layered double metal hydroxide with a higher metal ion valence state is prepared, which provides a large specific surface area for the dispersion of platinum particles, reduces the amount of precious metal platinum, and avoids the problems of catalyst loss and high resistance caused by the use of binders.

[0025] (4) The platinum / nickel-iron layered double hydroxide / foamed iron-nickel material obtained in the present invention has the characteristics of low precious metal loading, rich active sites, high activity and stability. It is a dual-functional electrode that can be used for both hydrogen evolution reaction and oxygen evolution reaction. It also provides guidance for the in-situ preparation of high-performance and stable electrodes, and has broad application prospects in the fields of energy and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0027] Figure 1 This is a scanning electron microscope image of the nickel-iron layered double hydroxide material with platinum particles grown on the surface of the nickel-iron foam prepared in Example 1.

[0028] Figure 2 This is an X-ray diffraction image of nickel-iron layered double metal hydroxide with platinum particles grown on the surface of the nickel-iron foam prepared in Example 1.

[0029] Figure 3 This is a transmission electron microscope image of the nickel-iron layered double hydroxide immobilized with platinum particles prepared in Example 1.

[0030] Figure 4 This is a high-resolution transmission electron microscope image of the nickel-iron layered double hydroxide loaded with platinum particles prepared in Example 1.

[0031] Figure 5 This is a high-resolution transmission electron microscope image of the nickel-iron layered double hydroxide loaded with platinum particles prepared in Example 1.

[0032] Figure 6 Polarization curves of the oxygen evolution reaction of the electrodes prepared in Example 1 and Example 2 in 1.0 M KOH solution.

[0033] Figure 7 Polarization curves of the oxygen evolution reaction of the electrodes prepared in Example 1 and Example 3 in 1.0 M KOH solution.

[0034] Figure 8 Polarization curves of the electrodes prepared in Example 1 and Example 4 for hydrogen evolution reaction in 1.0 M KOH solution.

[0035] Fig. 9 The polarization curves of the electrodes prepared in Example 1, Example 3 and Example 4 for the complete decomposition of water in 1.0 M KOH solution.

[0036] Fig.10 This is the chronoamperometry curve of the electrode prepared in Example 1 in the complete decomposition of water in 1.0 M KOH solution.

[0037] Fig.11 Polarization curves of the oxygen evolution reaction of the electrodes prepared in Example 1 and Example 8 in 1.0 M KOH solution. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0039] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0041] Example 1

[0042] Preparation of platinum / NiFe LDH / foam nickel iron (Pt / NiFe LDH / INF) composite electrode:

[0043] A foamed iron-nickel sheet (Fe:Ni=3:7, purchased from Suzhou Willtech Optoelectronic Materials Co., Ltd.) with a pore size of 0.1 mm, a porosity of 95-98%, and a thickness of 0.1 mm, with a length×width=1 cm×2 cm, was immersed in a 3M hydrochloric acid solution for 10 minutes under ultrasonication, and then the foamed iron-nickel substrate was cleaned with water, acetone, and ethanol, respectively;

[0044] The cleaned nickel-iron foam was immersed in a sample tube containing 7 ml of chloroplatinic acid solution (3.2 ml of ethanol, 3.1 ml of ethylene glycol diethyl ether and 0.7 ml of water, the amount of chloroplatinic acid added was calculated based on the theoretical mass loading of platinum being 1%, and the pH value of the solution was 2.5), and kept in a water bath at 85°C for 4 h;

[0045] After cooling to room temperature, the electrode was washed with ethanol and water and dried in a vacuum oven at 40 °C for 2 h.

[0046] Figure 1 This is a scanning electron microscope image of NiFe LDH on the surface of the nickel-iron foam prepared in this embodiment. It can be seen that the nanosheets grow vertically on the surface of the nickel foam sheet and intersect (or cross) with each other. The thickness of the nanosheets intersecting each other is 100-2000nm, the thickness of the nanosheets is 20-300nm, and the length between the farthest two points of the nanosheet is 500-2000nm.

[0047] Figure 2This is the X-ray diffraction image of NiFe LDH on the surface of the nickel-iron foam prepared in this embodiment. Compared with the standard card (pdf#40-0215), the signals at 11.4°, 23.0°, 34.3°, 38.9°, 46.0°, 59.9°and 61.2° are attributed to the characteristic diffraction peaks of NiFe LDH, confirming that the nanosheet is NiFe LDH.

[0048] Figure 3 This is a transmission electron microscope image of the NiFe LDH prepared in this example, and the layered morphology of nickel-iron hydroxide nanosheets can be seen.

[0049] Figure 4 This is a high-resolution transmission electron microscope image of the NiFe LDH loaded with platinum nanoparticles prepared in this example. The image shows that platinum nanoparticles are embedded on the surface of the NiFe LDH, with an average particle size of about 3 nm and a particle size distribution range of 2-10 nm.

[0050] Figure 5 This is a high-resolution transmission electron microscopy image of the NiFe LDH loaded with platinum nanoparticles prepared in this example, wherein the interplanar spacings of 0.258 and 0.229 correspond to the (012) and (015) planes of the NiFe LDH, respectively, confirming the composition of the nanosheets; the interplanar spacing of 0.226 nm is attributed to the (111) plane of the platinum particles, confirming that the nanoparticles on the surface of the NiFe LDH are platinum.

[0051] Example 2 (iron:nickel ratio of the foamed iron-nickel substrate is 5:5 and 7:3)

[0052] The operation steps are the same as those in Example 1, except that the iron-nickel foams with different iron-nickel ratios of 5:5 and 7:3 are used.

[0053] A foamed iron-nickel sheet (Fe:Ni=5:5 and Fe:Ni=7:3, both purchased from Suzhou Willtech Optoelectronic Materials Co., Ltd.) with a pore size of 0.1 mm, a porosity of 95-98%, and a thickness of 0.1 mm, with a length×width=1 cm×2 cm, was immersed in a 3M hydrochloric acid solution for 10 minutes by ultrasound, and then the foamed iron-nickel substrate was cleaned with water, acetone, and ethanol, respectively;

[0054] The cleaned iron-nickel foams (Fe:Ni=5:5 and Fe:Ni=7:3) were immersed in sample tubes containing 7 ml of chloroplatinic acid solution (3.2 ml of ethanol, 3.1 ml of ethylene glycol diethyl ether and 0.7 ml of water, pH value of the solution was 2.5) and kept in a water bath at 85°C for 4 h.

[0055] After cooling to room temperature, the electrode was washed with ethanol and water and dried in a vacuum oven at 40 °C for 2 h.

[0056] Example 3 (Preparation of a Typical Commercial OER Catalyst RuO2 / Fe-Ni Foam Electrode)

[0057] A foamed iron-nickel sheet (Fe:Ni=3:7) with a pore size of 0.1 mm, a porosity of 95-98%, and a thickness of 0.1 mm and a length×width=2 cm×3 cm was immersed in a 3M hydrochloric acid solution for 10 minutes under ultrasonication, and then the foamed iron-nickel substrate was cleaned with water, acetone, and ethanol, respectively;

[0058] Weigh 4.5 mg of RuO2 powder, add it to 900 μL of ethanol, ultrasonicate for 5 min, then add 25 μL of Nafion, ultrasonicate for 30 min, then drop it evenly on the surface of the foamed iron-nickel substrate and dry it to obtain a RuO2 / foamed iron-nickel (RuO2 / INF) electrode.

[0059] Example 4 (Preparation of a Typical Commercial HER Catalyst Pt / C / Foamed Iron-Ni Electrode)

[0060] A foamed iron-nickel sheet (Fe:Ni=3:7) with a pore size of 0.1 mm, a porosity of 95-98%, and a thickness of 0.1 mm and a length×width=2 cm×3 cm was immersed in a 3M hydrochloric acid solution for 10 minutes under ultrasonication, and then the foamed iron-nickel substrate was cleaned with water, acetone, and ethanol, respectively;

[0061] 4.5 mg of Pt / C powder was weighed and added to 900 μL of ethanol, and ultrasonicated for 5 min. Then 25 μL of Nafion was added and ultrasonicated for 30 min. Then, it was evenly dropped on the surface of the foamed nickel substrate and dried to obtain a Pt / C / foamed nickel iron (Pt / C / INF) electrode.

[0062] Example 5

[0063] Application of the platinum / NiFe LDH / foamed nickel iron material prepared in Example 1 as an oxygen evolution reaction (OER) catalyst:

[0064] A 0.5 × 1 cm platinum / NiFe LDH / foamed nickel electrode was used as the working electrode, a carbon rod was used as the counter electrode, and Hg / HgO was used as the reference electrode. The test was carried out using a CHI660E electrochemical workstation in 1.0 M KOH electrolyte solution.

[0065] Linear sweep voltammetry (LSV) was used with a scan rate of 5 mV s -1 , ohmic compensation is 85%, and polarization curves are obtained to analyze oxygen evolution performance.

[0066] The testing method for the OER polarization curves of the electrodes prepared in Example 2 and Example 3 is the same as above.

[0067] Figure 6 The OER polarization curves of the foamed iron-nickel substrates with Fe:Ni ratios of 3:7 (Example 1), 5:5 (Example 2) and 7:3 (Example 2) are shown in the figure. As can be seen from the figure, at the same current density, when the Fe:Ni ratio is 3:7, the platinum / NiFe LDH / foamed iron-nickel electrode prepared in this example has a current density of 10, 100 and 200 mA cm, respectively. -2 When , its oxygen evolution overpotential is only 201, 274 and 305 mA, which has the lowest overpotential, indicating that it has the lowest energy consumption and high oxygen evolution activity.

[0068] Figure 7 The OER polarization curves of the foamed nickel-iron substrate of platinum / NiFe LDH / foamed nickel-iron (Pt / NiFe LDH / INF, Example 1) and RuO2 / foamed nickel-iron (RuO2 / INF, Example 3) are shown in the figure. As can be seen from the figure, at the same current density, when the Fe:Ni ratio is 3:7, the Pt / NiFe LDH / INF electrode prepared by the method has a high current density of 10, 100 and 200 mA cm, respectively. -2 When , its oxygen evolution overpotential is only 201, 274 and 305 mA, which has the lowest overpotential, indicating that it has high oxygen evolution activity.

[0069] Example 6

[0070] Application of the platinum / NiFe LDH / foam nickel iron (Pt / NiFe LDH / INF) material prepared in Example 1 as a hydrogen evolution reaction (HER) catalyst:

[0071] A 0.5 × 1 cm platinum / NiFe LDH / foamed nickel electrode was used as the working electrode, a carbon rod as the counter electrode, and Hg / HgO as the reference electrode. The test was carried out using a CHI660E electrochemical workstation in a 1.0 M KOH electrolyte solution;

[0072] Linear sweep voltammetry (LSV) was used with a scan rate of 5 mV s -1 , ohmic compensation is 85%, and polarization curves are obtained to analyze hydrogen evolution performance.

[0073] The testing method for the HER polarization curve of the electrode (Pt / C / INF) prepared in Example 4 is the same as above.

[0074] Figure 8The OER polarization curves of the foamed nickel-iron substrate of platinum / NiFe LDH / foamed nickel-iron (Pt / NiFe LDH / INF, Example 1) and Pt / C / foamed nickel-iron (Pt / C / INF, Example 4) are shown in the figure. As can be seen from the figure, at the same current density, when the Fe:Ni ratio is 3:7, the Pt / NiFe LDH / INF electrode prepared by the method has a current density of 20, 100 and 200 mA cm, respectively. -2 When , its hydrogen evolution overpotential is only 20, 69 and 107 mA, which has the lowest overpotential, indicating that it has higher hydrogen evolution activity than Pt / C / INF.

[0075] Example 7

[0076] The platinum / NiFe LDH / nickel iron foam (Pt / NiFe LDH / INF) material prepared in Example 1 was used as both a hydrogen evolution reaction (HER) and an oxygen evolution reaction (OER) electrode to study its overall water splitting performance: two 0.5 × 1 cm platinum / NiFe LDH / nickel iron foam electrodes were cut out, and a two-electrode system was adopted, one as the cathode (HER) and one as the anode (OER), and the test was carried out using a CHI660E electrochemical workstation in a 1.0 M KOH electrolyte solution.

[0077] Linear sweep voltammetry (LSV) was used with a scan rate of 5 mV s -1 , ohmic compensation is 85%, and polarization curves are obtained to analyze the full water splitting performance.

[0078] In addition, the RuO2 / foamed nickel iron electrode prepared in Example 3 was used as the anode, and the Pt / C / foamed nickel iron electrode prepared in Example 4 was used as the cathode to analyze the overall water splitting performance of this system, and the test method was the same as above.

[0079] Fig. 9 This is the polarization curve of the complete water splitting tested in this example; it can be seen from the figure that when the Pt / NiFe LDH / INF prepared by this method is used as the cathode and anode, if it is to reach 10 and 100 mA cm -2 The current density only requires the addition of 1.44 and 1.58 volts;

[0080] When Pt / C / INF is used as cathode and RuO2 / INF is used as anode, a higher voltage is required to reach 10 and 100 mA cm -2 The current density increases the energy consumption.

[0081] Fig.10 The chronopotentiometry test of the complete water splitting with Pt / NiFe LDH / INF as cathode and anode. As can be seen from the figure, this complete water splitting system can be used at a current density of 20 mA cm -2It can be maintained for at least 16 hours with good stability.

[0082] Example 8

[0083] Using nickel foam (NF) as the substrate, a platinum-modified nickel-iron hydroxide (Pt / NiFe(OH)) was prepared on the surface of nickel foam by adding an iron ion source. x / NF) composite electrode and its performance as oxygen evolution reaction (OER) electrode:

[0084] A nickel foam sheet (purchased from Suzhou Willtech Optoelectronic Materials Co., Ltd.) with a pore size of 0.1 mm, a porosity of 95-98%, and a thickness of 0.1 mm and a length × width = 1 cm × 2 cm was immersed in a 3M hydrochloric acid solution for 10 minutes, and then the nickel foam substrate was cleaned with water, acetone, and ethanol, respectively;

[0085] The cleaned nickel foam was immersed in a sample tube containing a precursor solution (pH 2.5) containing 7 ml of chloroplatinic acid (3.2 ml of ethanol, 3.1 ml of ethylene glycol diethyl ether and 0.7 ml of water, the amount of chloroplatinic acid added was calculated based on the theoretical mass loading of platinum being 1%) and ferrous chloride (the amount of ferrous chloride added was calculated based on the theoretical mass loading of iron being 3%), and kept at 85°C in a water bath for 4 h;

[0086] After cooling to room temperature, the electrode was washed with ethanol and water and dried in a vacuum oven at 40 °C for 2 h.

[0087] The electrode prepared in this example is used as an oxygen evolution reaction (OER) electrode, and the method for testing its OER performance is the same as that in Example 5.

[0088] like Fig.11 As shown, under the same current density, the Pt / NiFe(OH) prepared in this example x Compared with the Pt / NiFe LDH / INF electrode in Example 1, the overpotential of the NiFe / NF electrode is larger, which means greater energy consumption and poor OER activity. This shows that the foamed iron-nickel substrate selected in this method is necessary, as it serves as a source of nickel ions and iron ions, and also has an important influence on the OER reaction.

[0089] It can be seen from the above examples that, through a simple one-step method, nickel-iron layered double hydroxides immobilized with platinum metal nanoparticles can be in situ grown on a foamed nickel-iron substrate. In an alkaline electrolyte solution, compared with the typical commercial oxygen evolution reaction catalyst RuO2, the platinum / NiFe LDH / foamed nickel-iron electrode prepared by this method has better oxygen evolution reaction activity; compared with the typical commercial hydrogen evolution reaction catalyst Pt / C, the platinum / NiFe LDH / foamed nickel-iron electrode prepared by this method has better hydrogen evolution reaction activity; compared with the typical full water splitting performance test with RuO2 as anode and Pt / as cathode, the platinum / NiFe LDH / foamed nickel-iron prepared by this method has higher full water splitting activity, lower overpotential, and better stability when used as both cathode and anode.

[0090] A one-step method is adopted to immerse the foamed iron-nickel substrate in an acidic solution of ether containing chloroplatinic acid, without the need to add nickel ions or / and iron ion salts, and by heating for a certain period of time, a nickel-iron layered double metal hydroxide mixed material modified by platinum nanoparticles is grown in situ on the surface of the foamed iron-nickel. The present invention does not require the high temperature and high pressure preparation conditions of the traditional hydrothermal method, has low equipment requirements, does not require the additional addition of nickel ion salts, relies on the oxidation ability of protonic acid to oxidize metal nickel and metal iron into nickel ions and iron ions, and prepares nickel-iron layered double metal hydroxides with higher metal ion valence states, provides a large specific surface area for the dispersion of platinum particles, and avoids the problems of catalyst loss and large resistance caused by the use of binders. The platinum / nickel-iron layered double metal hydroxide / foamed iron-nickel material obtained by the present invention has the characteristics of low precious metal loading, rich active sites, high activity and stability, and also provides guidance for the in-situ preparation of high-performance and stable electrodes, and has broad application prospects in the fields of energy and catalysis.

[0091] The present invention utilizes foamed iron nickel as a base material and a source of nickel ions and iron ions at the same time, does not require complicated operations and the addition of sacrificial agents, and importantly avoids the addition of doping substances, so that pure iron-nickel double hydroxides can be prepared. And further, by introducing a chloroplatinic acid precursor, the present invention realizes the one-step preparation of a platinum-modified nickel-iron layered double hydroxide material under mild conditions, and has high oxygen evolution and hydrogen evolution dual functional activities. Taking metal foamed iron nickel as an example, it is placed in an acidic ether solution containing a chloroplatinic acid precursor, and the metal nickel and iron on the surface of the foamed iron nickel are oxidized into nickel ions and iron ions by the proton acid in the solution, and the metal ions are hydrolyzed into iron-nickel hydroxides, and the chloroplatinic acid is reduced into platinum nanoparticles. The method of the present invention is used for in-situ preparation of a dual-functional platinum / nickel-iron layered double hydroxide / foamed iron-nickel electrode material with high activity for both hydrogen evolution reaction and oxygen evolution reaction in alkaline water electrolysis. No additional nickel ion or / and iron ion salt and sacrificial agent are required during the preparation process, the atom economy is good, the reaction conditions are mild, the energy consumption is low, and the problem of easy detachment of the catalyst caused by multiple operations and washing is avoided. The present invention effectively avoids the addition of metal salt sacrificial agents, thereby achieving the successful preparation of pure and undoped bifunctional electrode catalysts, while reducing the amount of precious metal platinum, can be carried out under mild conditions, has a simple process, and is conducive to scale-up production.

[0092] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a dual-functional nickel-iron layered double hydroxide material modified by in-situ growth of platinum on the surface of nickel-iron foam, characterized in that: include, The metal foamed nickel iron is placed in an acidic solution containing a chloroplatinic acid precursor and subjected to a heating treatment to obtain nickel-iron layered double metal hydroxide nanosheets with platinum metal nanoparticles immobilized on the surface of the metal foamed nickel iron.

2. The preparation method according to claim 1, characterized in that: The acidic solution containing the chloroplatinic acid precursor is composed of an ether compound, an alcohol compound and water, and the volume ratio of the ether, the alcohol and the water is (2:7:1) to (5:2:3).

3. The preparation method according to claim 2, characterized in that: The ether compound includes one or more of ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, diethylene glycol diethyl ether, and n-butyl ether; The alcohol compound includes one or more of methanol, ethanol, propanol, isopropanol, butanol, ethylene glycol, and glycerol.

4. The preparation method according to claim 3, characterized in that: The pH value of the acidic solution is 1-6.

5. The preparation method according to claim 1, characterized in that: The chloroplatinic acid precursor is a chloride, nitrate and carbonate of platinum, including chloroauric acid, potassium chloroaurate, sodium chloroaurate, ammonium chloroaurate, chloroplatinic acid, sodium chloroplatinate, potassium chloroplatinate, platinum chloride, potassium chloroplatinite, sodium chloroplatinite, diethylamine platinum chloride, platinum nitrate, ammonium tetrachloroplatinate, ammonium chloropalladate, sodium chloropalladate, potassium chloropalladate, ammonium chlororhodate, sodium chlororhodate, potassium chlororhodate, chloroiridic acid, sodium chloroiridate, potassium chloroiridate, rhodium trichloride, ruthenium trichloride, cupric chloride and cuprous chloride.

6. The preparation method according to claim 1 or 5, characterized in that: In the metal foam iron-nickel, the weight ratio of iron to nickel is 0-1, excluding 0 and 1.

7. The preparation method according to claim 6, characterized in that: In the metal foam iron-nickel, the weight ratio of iron to nickel is 3:

7.

8. The preparation method according to claim 1, characterized in that: The temperature of the heating treatment process is 0 to 200° C. and the time is 0 to 24 hours.

9. A nickel-iron layered double hydroxide bifunctional material electrode with platinum modified in situ growth on the surface of nickel-iron foam obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the electrode according to claim 9 in hydrogen evolution and oxygen evolution reactions by electrolysis of water under alkaline conditions.

Citation Information

Patent Citations

  • Foamed nickel supported nickel-iron bimetallic oxyhydroxide composite catalyst as well as preparation method and application thereof

    CN114643057A

  • Foamed ferronickel-based electrolyzed water bifunctional catalyst and preparation method thereof

    CN116949494A

  • Method for preparing ferronickel layered double-metal hydroxide material on surface of foamed ferronickel

    CN117385396A

Cited By

  • Method for preparing platinum-loaded monatomic electrode through electro-deposition and electrode

    CN120138675A

  • Preparation method of noble metal atom anchored hydroxide-based oxygen evolution electrode

    CN121137647A

  • Cobalt-nickel-iron ternary metal phosphide electro-catalysis electrode based on foam iron-nickel carrier as well as preparation method and application of cobalt-nickel-iron ternary metal phosphide electro-catalysis electrode

    CN122564630A